Developing Digital-Based Speaking Literacy Assessment Using PLOMP Model to Support the National Literacy Movement - Maitri Rahmadhani; Supriadi Supriadi (Institut Agama Islam Negeri Palopo, 2022)
This research aimed to develop a digital-based speaking literacy assessment that credible, measurable and doable by using PLOMP model in an effort to support the National Literacy Movement. The problem of this research were to find out whether: a. the digital-based speaking literacy assessment that has been developed is practical and valid to solve the problem? b. the use of digital-based speaking literacy assessment that has been developed is effective? Research and Development (R&D) method was used as the design of this research by implementing the PLOMP Model. The instrument of this research were questionnaires that were given to the expert validators and the teachers. The result showed that: a. the digital-based speaking literacy assessment is valid (90.88%), 85.5% respondents respond positively to the digital-based speaking literacy assessment including its interest and its attractiveness, c. It indicated that the developed digital-based speaking literacy assessment model has fulfill the aspect of feasibility and effectiveness and has been tested successfully implemented at SMK Al Maksum Stabat